The methyltransferase Ezh2 controls cell adhesion and migration through direct methylation of the extranuclear regulatory protein talin - Ginhoux, Florent (2015)
A cytosolic role for the histone methyltransferase Ezh2 in regulating lymphocyte activation has been suggested, but the molecular mechanisms underpinning this extranuclear function have remained unclear. Here we found that Ezh2 regulated the integrin signaling and adhesion dynamics of neutrophils and dendritic cells (DCs). Ezh2 deficiency impaired the integrin-dependent transendothelial migration of innate leukocytes and restricted disease progression in an animal model of multiple sclerosis. Direct methylation of talin, a key regulatory molecule in cell migration, by Ezh2 disrupted the binding of talin to F-actin and thereby promoted the turnover of adhesion structures. This regulatory effect was abolished by targeted disruption of the interactions of Ezh2 with the cytoskeletal-reorganization effector Vav1. Our studies reveal an unforeseen extranuclear function for Ezh2 in regulating adhesion dynamics, with implications for leukocyte migration, immune responses and potentially pathogenic processes.